2017
DOI: 10.18001/trs.3.2(suppl1).8
|View full text |Cite
|
Sign up to set email alerts
|

Dual Use of Cigarettes, Little Cigars, Cigarillos, and Large Cigars: Smoking Topography and Toxicant Exposure

Abstract: Objective-Smoking topography variables and toxicant exposure (plasma nicotine and exhaled CO) were examined in 3 groups of study participants that smoked both cigarettes and either filtered little cigars (Winchester), cigarillos (Black & Mild), or large cigars (Phillies Blunt).Methods-Laboratory ad lib smoking of the cigar products was collected with a smoking puff analyzer; plasma levels of nicotine and exhaled CO were collected before and after smoking.Results-Although there were no statistically significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 34 publications
3
29
0
Order By: Relevance
“…Our findings may also be explained by differences in nicotine delivery. For example, a recent study found higher levels of plasma nicotine per unit of consumption from little cigar smoking compared with cigarillo or large cigar smoking (31). We observed that TNE-2 concentrations in every day exclusive filtered cigar smokers were comparable to those of every day exclusive cigarette smokers.…”
Section: Discussionsupporting
confidence: 54%
“…Our findings may also be explained by differences in nicotine delivery. For example, a recent study found higher levels of plasma nicotine per unit of consumption from little cigar smoking compared with cigarillo or large cigar smoking (31). We observed that TNE-2 concentrations in every day exclusive filtered cigar smokers were comparable to those of every day exclusive cigarette smokers.…”
Section: Discussionsupporting
confidence: 54%
“…This suggested EC was less popular for PTU. Dual use of cigar and cigarette was associated with less negative perception toward cigarette use and quit attempts [ 27 ], tobacco intervention program specific to this subgroup of smokers is warranted to prevent the growth of this type of PTU. The trend changes in overall prevalence of number of tobacco product use with cigarette varied in 3 years, this suggested these smoking behaviors had not been routinized.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested EC was less popular for PTU and those who used EC were more likely to be exclusive EC users. Dual use of cigar and cigarette was associated with less negative perception toward cigarette use and quit attempts, 27 tobacco intervention program speci c to this subgroup of smokers is warranted to prevent the growth of this type of PTU. The trend changes in overall prevalence of number of tobacco product use with cigarette varied in three years, this suggested these smoking behaviors had not been routinized.…”
Section: Discussionmentioning
confidence: 96%